Behaviour and design of slender built-up nested cold-formed steel compression members. (15th August 2021) - Vy, Son Tung; Mahendran, Mahen
Highlights: Investigated the behaviour of slender screw-fastened nested channel (NC) members. Torsional and flexural–torsional buckling are not critical for NC members. NC member capacity can be higher than the sum of individual capacities in some cases. Effects of screw fastener arrangements and end group fasteners are marginal. Proposed a simplified and reliable design method based on the current DSM equations. Abstract: Built-up nested channel (NC) members, which are made of asymmetric cold-formed steel (CFS) lipped channel sections are commonly used in various building applications in Australia. The aim of this research study is to provide suitable design guidelines for NC compression members, which fail by global or local–global interaction buckling. Firstly, the design rules in the current CFS design standards and recently published research studies were reviewed, and their limitations for NC members were discussed. A test series was then conducted on single channel and NC compression members, which failed by local–global interaction buckling. Based on the test results, validated finite element (FE) models were developed, followed by a detailed parametric study of NC members failing in global or local–global interaction buckling for different sections, lengths, end support boundary conditions as well as screw sizes and arrangements. The test and FE analysis results were used to: (1) compare the compression capacities of NC members with the sum of their individual member capacities, (2) evaluate the effect of screw characteristics and arrangements, and (3) investigate the design methods in the current design standards and past research studies. Finally, based on the Direct Strength Method in the current design standards, a simple and reliable design method was proposed. This paper presents the details of this research study and the results including its findings.